Medical Students’ Knowledge and Attitudes Toward Shared Decision Making: Results From a Multinational, Cross-Sectional Survey - Yen, Renata W. (MDM Policy Pract, 2019)
Introduction. We aimed to conduct a multinational cross-sectional online survey of medical students’ attitudes toward, knowledge of, and experience with shared decision making (SDM). Methods. We conducted the survey from September 2016 until May 2017 using the following: 1) a convenience sample of students from four medical schools each in Canada, the United States, and the Netherlands (n = 12), and 2) all medical schools in the United Kingdom through the British Medical School Council (n = 32). We also distributed the survey through social media. Results. A total of 765 students read the information sheet and 619 completed the survey. Average age was 24, 69% were female. Mean SDM knowledge score was 83.6% (range = 18.8% to 100%; 95% confidence interval [CI] = 82.8% to 84.5%). US students had the highest knowledge scores (86.2%, 95% CI = 84.8% to 87.6%). The mean risk communication score was 57.4% (range = 0% to 100%; 95% CI = 57.4% to 60.1%). Knowledge did not vary with age, race, gender, school, or school year. Attitudes were positive, except 46% believed SDM could only be done with higher educated patients, and 80.9% disagreed that physician payment should be linked to SDM performance (increased with years in training, P < 0.05). Attitudes did not vary due to any tested variable. Students indicated they were more likely than experienced clinicians to practice SDM (72.1% v. 48.8%). A total of 74.7% reported prior SDM training and 82.8% were interested in learning more about SDM. Discussion. SDM knowledge is high among medical students in all four countries. Risk communication is less well understood. Attitudes indicate that further research is needed to understand how medical schools deliver and integrate SDM training into existing curricula.